Arterite viral eqüina no Estado de Minas Gerais. - Ana Cristina Passos de Paiva Bello (2006)
The equine viral arteritis infects equides and his control is very important to equideoculture. This infection has been reported in several countries, but there are only a few studies in Brazil. This work intended to verify the frequency and distribution of the disease in ten regions of Minas Gerais State using the test of seroneutralization. The results obtained showed a tax (0.85%) of all the samples (7/826), while the founds in the regions were: Almenara (0.77%), Montes Claros (1.09%), Oliveira (2.12%), São Gonçalo do Sapucaí (2.22%), Teófilo Otoni (1.36%) and Viçosa (1.72%). The regions of Bambuí, Curvelo, Governador Valadares e Unaí theres no animal reagent. Characterizing, therefore, the contact of equides with the virus of the equine viral arteritis in seven of ten investigated regions of Minas Gerais State.